Attributes encoded by OFC neurons. - Aster Q. Perkins (22008260) (2025)
(a) Types of attribute encoding in six example neurons. Lines show signed coefficient estimates for chosen or unchosen sweetness (Swt) or probability (Prob) over time. Thick segments denote regions of significance (p ≤ 0.01 × 3 consecutive time bins). Top row left to right: A neuron encoding both sweetness and probability of the chosen option. A neuron whose firing rate varies with all four attributes. Middle row: Neurons encoding the chosen sweetness only (left) or chosen probability only (right). Bottom row: Neurons whose firing rates vary with both chosen and unchosen sweetnesses (left) or probabilities (right). (b) Proportion of neurons with different encoding patterns. (c) Schematic showing relative value of an attribute that is discordant with the chosen options. The choice is between a low (level 2) sweetness and high (level 5) probability vs. a high (level 4) sweetness and low (level 2) probability, and the first option is selected. Only direct mappings are shown for simplicity. The chosen/unchosen model would assign attribute values for chosen sweetness, chosen probability, unchosen sweetness, unchosen probability as [2 5 4 2], but the better/worse model for the same trial would assign better sweetness, better probability, worse sweetness, worse probability as [4 5 2 2]. (d) Proportion of neurons assigned to each model. (e) Neurons assigned to the best/worst (purple) or chosen/unchosen (green) model over time, sorted by the time of better/worse encoding. Many neurons shifted from encoding better/worse attributes early and chosen/unchosen attributes later. (f–g) There were no correlations between beta coefficients for chosen and unchosen attributes or better and worse attributes.